KEBIJAKAN THE NEW SILK ROAD CINA DI BAWAH PEMERINTAHAN XI JINPING - Ni Putu Saraswati Puspita Dewi; Hikmatul Akbar (Jurnal Studi Diplomasi dan Keamanan, 2017)
Silk Road is an ancient trade route that connecting China and countries along Asia and Europe. China under President Xi Jinping wants to rebuild the ancient silk road by building various infrastructure such as highways, railways, ports, and gas pipelines. The development of this infrastructure aims to increase connection of Asian, European and African countries. "The New Silk Road: One Belt One Road" is the name of policy on rebuilding this road. In realizing this policy, China does many cooperations with various countries in the region and invests huge funds for several major projects. Beyond that, China has various interests in construction of The New Silk Road which will be profitable for China both in economic and politics